Control of Chaos in a Single Machine Infinite Bus Power System Using the Discrete Sliding Mode Control Technique - Mohamed Zribi; Muthana T. Alrifai; Nejib Smaoui (Discrete Dynamics in Nature and Society)
Under certain conditions, power systems may exhibit chaotic behaviors which are harmful and undesirable. In this paper, the discrete time sliding mode control technique is used to control a chaotic power system. The objective of the control is to eliminate the chaotic oscillations and to bring order to the power system. Two discrete time sliding mode control (DSMC) schemes are proposed for a fourth order discrete time chaotic power system. The first DSMC control scheme is based on the well-known exponential reaching law. The second DSMC control scheme is based on the recently developed double power reaching law. It is shown that the states of the controlled system converge to their desired values. Simulation results are presented for different values of the gains of the controllers as well as for different initial conditions. These results indicate that both control schemes work well. However, the simulation results show that the second control scheme gave better results since it was able to greatly reduce the chattering problem.